Focus in Limbum - Becker, Laura; Driemel, Imke; Awasom, Jude Nformi (My University, 2019)
In this paper, we discuss the realization of focus in Limbum (Grassfields Bantu, Cameroon), a language which shows a so-far unattested pattern of focus marking, where two distinct focus constructions are realized by two different particles, á and bá, which express information focus on the one hand and contrastive focus on the other. Strikingly, the former is realized by a structurally more complex construction (particle + fronting) – the inverse pattern of what is attested cross linguistically (Fiedler et al. 2010; Skopeteas & Fanselow 2009). A biclausal cleft structure underlying the á strategy can be argued to be implausible. Instead, we adopt a Q/F particle analysis (Cable 2010) which proposes the existence of a particle independent of a higher functional head mediating between that head and the focused phrase. Limbum provides overt evidence for both, the head and the particle.
Keywords: Limbum; focus markers; focus